2006
DOI: 10.1310/hpj4107-659
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of a Fentanyl, Morphine, and Hydromorphone Patient-Controlled Intravenous Delivery for Acute Postoperative Analgesia: A Multicenter Study of Opioid-Induced Adverse Reactions

Abstract: Patient-controlled analgesia (PCA) is a widely used delivery system for intravenous (IV) administration of opioids during acute post-operative pain management. Various opioids have been used for IV PCA including morphine, meperidine, hydromorphone, and fentanyl. Morphine is by far the most commonly used opioid in this setting, yet the selection of morphine as the primary opioid is based largely on tradition. Meperidine should not be considered in the PCA armamentarium due to the associated risk of central nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 7 publications
3
34
0
Order By: Relevance
“…Other analgesic techniques, such as epidural infusions and continuous femoral blocks, may also be used [8]. However, multimodal analgesia has been established as the preferred method for postoperative pain control [9,10], and studies have shown that multimodal analgesia that includes infiltration of a local anesthetic administered during total knee arthroplasty provides better postsurgical pain control than monotherapy-based regimens. This approach is also associated with a reduction in the use of opioid analgesics, leading to fewer opioidrelated adverse events (AEs) [8,[11][12][13][14] such as respiratory depression, hypotension, nausea, vomiting, central nervous system depression, pruritus, and constipation.…”
Section: Introductionmentioning
confidence: 99%
“…Other analgesic techniques, such as epidural infusions and continuous femoral blocks, may also be used [8]. However, multimodal analgesia has been established as the preferred method for postoperative pain control [9,10], and studies have shown that multimodal analgesia that includes infiltration of a local anesthetic administered during total knee arthroplasty provides better postsurgical pain control than monotherapy-based regimens. This approach is also associated with a reduction in the use of opioid analgesics, leading to fewer opioidrelated adverse events (AEs) [8,[11][12][13][14] such as respiratory depression, hypotension, nausea, vomiting, central nervous system depression, pruritus, and constipation.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are effective, opioids have drawbacks that include respiratory depression, hypotension, nausea, vomiting, central nervous system depression, pruritus, and constipation. 15,16 Concerns about opioid-related complications can result in substantial undertreatment of acute pain and inappropriate postsurgical pain management. [17][18][19][20][21][22][23][24][25] A local analgesic providing adequate postsurgical pain relief for a longer duration than currently available agents could be a useful therapeutic option for the management of postsurgical pain.…”
mentioning
confidence: 99%
“…The major drugs used in this system are the opioid analgesics, such as morphine, hydromorphone, fentanyl, sufentanil and tramadol [31]. Meperidine is no longer considered a valid option for PCA as its toxic metabolite may be accumulated, especially in patients with abnormal kidney function [32].…”
Section: Intravenous Pca (Iv-pca)mentioning
confidence: 99%
“…As the M6G has renal elimination, the use of morphine should be done with caution in patients with impaired renal function and the elderly [34,35]. The low therapeutic index of morphine in IV-PCA was shown in preclinical models, indicating that morphine cannot be the best option for all patients for pain relief in the postoperative period [31].…”
Section: Morphinementioning
confidence: 99%